A-LIEP 2011: Building the Strategic Pillars for Angkatan Sasterawan 50‟s Online Information Services / Amirrudin Dahlan, Nurhazman Abdul Aziz, Mohd Pitchay Gani M. A. Aziz... [et.al]. - Dahlan, Amirrudin; Abdul Aziz, Nurhazman; M. A. Aziz, Mohd Pitchay Gani; Supa‘at, Juffri (2011)
In this practitioner‘s paper, we share why and how Angkatan Sasterawan‘ 50 (ASAS 50) has explored and embraced Web 2.0 technologies extensively to showcase the rich Malay‗s cultural and literacy materials from the past. At the same time, the integration of such technology and literacy will help to promote the preservation for the future generation in a conceited effort to raise their awareness of the core values and identities of where and who their fore-fathers‘ were. For a period of about six months, we have been spending time to comprehend the historical backdrop of ASAS 50. It includes the rationale of its creation and where it envisioned being in the future. And for the six months that followed, the actual work of design begun. Thus, we conceptualized a general model based on certain known ones such as Porter Five‘s Forces to shield ourselves from future coercion (Porter, 2008) and strategic alignment model from Henderson & Venkatraman (1993). The new website is paving ways for marrying new technology with the information needs of the organisation. This movement is to promote literacy to the young generation who are more technologically inclined and exposing them to the importance of the Malay‘s language, heritage and culture (Delamere, 1996). In order to align with the organisation needs and the technology adoption, ASAS 50 is ready to embrace new social technologies. During the initial phase, the site has received a healthy growth in visitor-ships. Social web systems have offered new opportunities for us to engage the community and produce better search relevancy. The paper only captures the sentiments of the local scene. However, our plan does include the foresight of reaching to other countries. Thus, the idea of the portal being conceived from the beginning adopting English as the main medium to break the language differences was a sound move. The content however remained authentic to its value of Malay roots. The paper recommends the steps of implementing social web components into the uncharted domain of the literacy world. It also highlights the success aspects that can be used for any future literacy and technology collaborations by interested parties.